The Periodic Location-Routing with Selective Recycling Problem: Two Solution Approaches⁎This study was financed by the regular project of DGI at the UNAB. Issue 1 (2021) - Flores-Carrasco, J.; Morillo-Torres, D.; Escobar, J.W.; Linfati, R.; Gatica, G.
Abstract: Waste collection is one of the most important processes in the main cities. Its current volume obliges governments to establish efficient measures to satisfy the collection offer. Over 70% of waste can be recycled. It is necessary to identify the collection centers, the routes to be followed either by minor collectors and/or vehicles, the specific day of collection, and an estimate of the volumes of waste to recycling. The problem has been mathematically modeled in the literature. However, they suffer from the differentiation of the type of waste and the day of collection. This paper presents a new variant of the classical routing problem, called the Periodic Location-Routing with Selective Recycling Problem. It considers collection centers, types of containers by-product, day of collection, and subsequent routing. Besides, two solution approaches are presented: first, a model based on mixed-integer programming, and second, a greedy constructive heuristic. Several sets of instances are proposed. Preliminary results are favorable, achieving to solve instances with up to 15 customers for the exact approach and experimenting up to 1000 customers with the heuristics. The model and the solution technique are scalable.